Exudate-responsive chlorine dioxide system reshapes microbial ecological dynamics for smart preservation of chilled mutton - Huan Huang; Peng Zhang; Wanting Shi; Hejun Yang; Chunbao Zhang; Wenxiu Sun (Food Research International, 2026)

Soil health index–based assessment of cadmium ecological risk–fertility coupling in seasonally frozen agricultural soils - Haoqin Yang; Haibing Wang; Hejun Zuo; Shichao Chen; Xiya Liu; Chengxian Liao; Xue Chen; Xu Liu; Siqi Li (Journal of Hazardous Materials, 2026)

Experimental investigation of helium gas heat exchangers for vibration and thermal noise control in closed-cycle cryostats - Shuo Yang; Hejun Hui; Yanyang Jiang; Meng Guo; Zhenhua Jiang; Yinong Wu; Shaoshuai Liu (International Journal of Refrigeration, 2026)

Quantitative resolution analysis in seismic imaging: From classical theory to cutting-edge advances - Jidong Yang; Jianping Huang; Hejun Zhu; Jiaxing Sun; Li-yun Fu; George McMechan; Houzhu Zhang; Ru-Shan Wu (Earth-Science Reviews, 2026)

In-situ remediation of Cr(VI) contaminated groundwater by synergistic oxalic acid-ethanol reduction: Mechanistic insights and sand tank validation - Wenwen Lin; Yang Liu; Zhonghui Han; Chengye Wang; Xiaoxu Zhang; Taigang Ma; Hejun Ren (Journal of Cleaner Production, 2025)

Fe(III)-MGDA complexation-mediated Fenton-like reaction for efficient degradation of metronidazole in simulated organic wastewater at neutral pH - Diansheng Wang; Hejun Ren; Yimei Sun; Chaoge Yang; Fangyuan Liu (Journal of Environmental Chemical Engineering, 2025)

Low-concentration lead stress enhanced the reproductive potential of Aleuroglyphus ovatus (Troupeau) (Acarina: Acaridae) by upregulating both the expression level and protein level of Vitellogenin gene - Hejun Liu; Hui Ai; Xi Wang; Yang Zou; Jinnan Zhang; Shanglin Zhong; Zhengtai Zhou; Tianrong Xin; Bin Xia; Zhiwen Zou (Experimental and Applied Acarology, 2025)

Dual-enzyme-responsive fibers for chilled mutton preservation - Yu Hao; Ruizhe Zhang; Chaoping Jiang; Hejun Yang; Zhang Peng; Wenxiu Sun (Food and Bioproducts Processing, 2025)

Saikosaponin a promotes neutrophil extracellular trap formation and bactericidal activity - Lanqiu Zhang; Zhengwei Hu; Lei Yang; Tianyu Liu; Jing Xun; Qi Zhang; Ximo Wang; Hejun Gao; Zhongkui Jin (Natural Product Research, 2025)

Enzyme-responsive bacteriostatic fibers loaded with thymol for chilled mutton preservation - Chaoping Jiang; Ruizhe Zhang; Yu Hao; Hanyuan Zhang; Hejun Yang; Peng Zhang; Wenxiu Sun (Food Research International, 2025)

Molecular cloning, expression and functional analysis of foxl2 from Chinese sturgeon (Acipenser sinensis) in relation to sex differentiation - Yacheng Hu; Ruihua Tan; Yang Li; Tingting Shu; Gang Yang; Zhong Chu; Haoran Wang; Xueqing Liu; Xin Zhu; Binzhong Wang; Baifu Guo; Runqiu Wang; et al. (Frontiers in Marine Science, 2024)
Introduction Our understanding of the regulatory mechanisms that govern the development of sexual characteristics in sturgeon, particularly the Chinese sturgeon (Acipenser sinensis), is limited. Foxl2, a member of the forkhead/HNF-3-related transcription factor family, is known for its role in precise gene regulation within specific tissues and its control over ovarian aromatase, a key enzyme in ovarian development and maturation. This study aimed to investigate the sexually dimorphic expression of foxl2 during the molecular and morphological sex differentiation stages in Chinese sturgeon. Methods We successfully isolated the full-length cDNAs of foxl2 in Chinese sturgeon. We then examined the expression profiles of this gene across various somatic tissues in both female and male specimens. Results Foxl2 was predominantly expressed in the ovulatory organs of two-year-old Chinese sturgeon, with significantly lower expression in other somatic tissues. We observed sexual dimorphism in foxl2 expression within gonads that had achieved morphological differentiation. Discussion The results suggest that foxl2 expression is intricately linked to the process of ovarian differentiation in Chinese sturgeon. Furthermore, we propose that the mRNA quantities of foxl2 could serve as an accurate biomarker for sex determination in sturgeon during their early growth stages.

Cadmium absorption and translocation in rice plants are influenced by lower air temperatures during grain filling stage - Xinzhen Zhang; Hang Xu; Jiangying Tang; Juan Yang; Zhiqiang Guo; Yang Xiao; Yulu Ge; Tian Liu; Qian Hu; Hejun Ao; Wanju Shi (Science of The Total Environment, 2024)

Cloning, identification, and functional analysis of foxl2 gene and its expression after 17β‐estradiol (E2) treatment in Dabry’s sturgeon, Acipenser dabryanus - Yacheng Hu; Ruihua Tan; Tingting Shu; Zhong Chu; Haoran Wang; Yining Chen; Xin Zhu; Yang Li; Binzhong Wang; Baifu Guo; Runqiu Wang; Huantao Qu; et al. (Frontiers in Marine Science, 2024)
The study focuses on the critically endangered Dabry’s sturgeon ( Acipenser dabryanus ), a species on the brink of extinction in the wild. This research investigates the role of the Forkhead box protein L2 ( foxl2 ) in the gonadal development and differentiation of this species. The foxl2 gene, known for its role in various physiological processes, including sexual maturation, is hypothesized to play a significant role in the sex differentiation of Dabry’s sturgeon. This study cloned the full-length cds sequence of the foxl2 gene and analyzed its expression across various tissues, focusing on its response to estradiol treatment. Our findings indicate that foxl2 is predominantly expressed in ovaries and shows a dose-dependent response to estradiol, suggesting its potential role in ovarian differentiation. This research underscores the importance of foxl2 in understanding reproductive biology and offers a foundation for future conservation strategies.

Understanding iodine adsorption sites on monolithic N/O co-doped carbon fibers with scaffolding structure - Hongquan Fu; Yue Tang; Qiao Yuan; Jingming Chang; Fang Liao; Juan Zhang; Hejun Gao; Yi Yang; Yunwen Liao (Fuel, 2024)

Enhanced capacitive deionization for Cr(VI) removal from electroplating wastewater: Efficacy, mechanisms, and high-voltage flow electrodes - Rui Zhou; Jingyang Li; Yunbo Dai; Fangyuan Liu; Shuzheng Yang; Hejun Ren; Chunpeng Zhang (Journal of Environmental Chemical Engineering, 2024)

Low-rank Representation for Seismic Reflectivity and its Applications in Least-squares Imaging - Jidong Yang; Jianping Huang; Hao Zhang; Jiaxing Sun; Hejun Zhu; George McMechan (Surveys in Geophysics, 2024)

RNA outperforms DNA-based metabarcoding in assessing the diversity and response of microeukaryotes to environmental variables in the Arctic Ocean - Hejun Kong; Eun-Jin Yang; Nianzhi Jiao; Youngju Lee; Jinyoung Jung; Kyoung-Ho Cho; Jong-Kuk Moon; Jee-Hoon Kim; Dapeng Xu (Science of The Total Environment, 2023)

High-Temporal-Accuracy Viscoacoustic Wave Propagation Based on k-Space Compensation and the Fractional Zener Model - Yabing Zhang; Tongjun Chen; Yang Liu; Hejun Zhu (Surveys in Geophysics, 2023)

Role of siderophore in Pseudomonas fluorescens biofilm formation and spoilage potential function - Jian Chen; Zhihua Sun; Jiamin Jin; Feifei Wang; Qing Yang; Hejun Yu; Jingyi Yu; Yanbo Wang (Food Microbiology, 2023)

Hydrogenation of dimethyl oxalate to ethanol over Mo-doped Cu/SiO2 catalyst - Zheng Li; Yihui Li; Xuepeng Wang; Yuan Tan; WenShao Yang; Hejun Zhu; Xingkun Chen; Wei Lu; Yunjie Ding (Chemical Engineering Journal, 2023)

Correction to: Mitigating Velocity Errors in Least-Squares Imaging Using Angle-Dependent Forward and Adjoint Gaussian Beam Operators - Jidong Yang; Jianping Huang; Zhenchun Li; Hejun Zhu; George McMechan; James Zhang; Yang Zhao (Surveys in Geophysics, 2022)

Geometry-preserving full-waveform tomography and its application in the Longmen Shan area - Xingpeng Dong; Dinghui Yang; Hejun Zhu; Yun Chen (Science China Earth Sciences, 2022)

Mitigating Velocity Errors in Least-Squares Imaging Using Angle-Dependent Forward and Adjoint Gaussian Beam Operators - Jidong Yang; Jianping Huang; Zhenchun Li; Hejun Zhu; George McMechan; James Zhang; Yang Zhao (Surveys in Geophysics, 2021)

Elastic Least-Squares Imaging in Tilted Transversely Isotropic Media for Multicomponent Land and Pressure Marine Data - Jidong Yang; Biaolong Hua; Paul Williamson; Hejun Zhu; George McMechan; Jianping Huang (Surveys in Geophysics, 2020)

Genome‐wide analysis of the Chinese sturgeon sox gene family: identification, characterisation and expression profiles of different tissues - Jing Yang; Yacheng Hu; Jilu Han; Kan Xiao; Xueqing Liu; Chun Tan; Qingkai Zeng; Hejun Du (Journal of Fish Biology, 2020)
The sox family is assumed to be responsible for a number of developmental systems. Genome sequencing technology makes it possible to scan sox genes and conduct characteristic analyses of different species. In fish, full characterisation of sox genes at the genome‐wide level has been reported for pufferfish Takifugu rubripes , medaka Oryzias latipes , tilapia Oreochromis niloticus and channel catfish Ictalurus punctatus . However, no systematic investigation of the sox family in sturgeons (Acipenseridae) has been reported to date. This study conducted genome‐wide identification of the sox genes in the Chinese sturgeon Acipenser sinensis and profiled their tissue distribution between male and female individuals. In total, 19 sox genes were identified, including soxb1 , b2 , c , d , e , f and h , in the Chinese sturgeon. Genomic structure analysis indicated relatively conserved exon–intron structures in each sox group and phylogenetic analysis supported the previous classification of the sox family. Most of the sox genes showed a tissue‐specific expression pattern, indicating the possible involvement of Chinese sturgeon sox genes at different developmental processes such as cardiac and gonadal development. This study provides a comprehensive resource of Chinese sturgeon sox genes and enables a better understanding of the evolution and function of the sox family.

Pseudomonas monteilii PN1: a great potential P-nitrophenol degrader with plant growth promoting traits under drought and saline–alkali stresses - Yuqin Zhang; Feng Yang; Hejun Ren; Jinliang Liu; Wenyang Mu; Yan Wang (Biotechnology Letters, 2019)

QTL Detection for Albinism-Related Loci in Chinese Tongue Sole (Cynoglossus semilaevis) - Yang Liu; Wenteng Xu; Bo Zhang; Changwei Shao; Xiaoxia Wang; Hejun Sun; Na Wang; Songlin Chen (Journal of Ocean University of China, 2018)

Genomic Selection Using BayesCπ and GBLUP for Resistance Against Edwardsiella tarda in Japanese Flounder (Paralichthys olivaceus) - Yang Liu; Sheng Lu; Feng Liu; Changwei Shao; Qian Zhou; Na Wang; Yangzhen Li; Yingming Yang; Yingping Zhang; Hejun Sun; Weiwei Zheng; Songlin Chen (Marine Biotechnology, 2018)

Enhancing bacterial transport with saponins in saturated porous media for the bioaugmentation of groundwater: visual investigation and surface interactions - Yongsheng Zhao; Dan Qu; Rui Zhou; Xinru Yang; Wenbo Kong; Hejun Ren (Environmental Science and Pollution Research, 2018)

Efficacy of forming biofilms by Pseudomonas migulae AN-1 toward in situ bioremediation of aniline-contaminated aquifer by groundwater circulation wells - Yongsheng Zhao; Dan Qu; Rui Zhou; Shuai Yang; Hejun Ren (Environmental Science and Pollution Research, 2016)

Cloning and characterisation of a novel 2,4-dichlorophenol hydroxylase from a metagenomic library derived from polychlorinated biphenyl-contaminated soil - Yang Lu; Ying Yu; Rui Zhou; Wei Sun; Chunyan Dai; Pei Wan; Lanying Zhang; Dongyun Hao; Hejun Ren (Biotechnology Letters, 2011)